1998
DOI: 10.1044/0161-1461.2903.172
|View full text |Cite
|
Sign up to set email alerts
|

Culture-Based Considerations in Programming for Stuttering Intervention With African American Clients and Their Families

Abstract: This article describes a clinical framework that may be used with African American children who stutter and their families. It includes discussion of the clinical importance of culture-based factors such as myths, oral presentation styles, narrative discourse styles, and cognitive learning styles, as well as rules for interaction and turn-taking. These factors are considered relative to the various clinical stages in the evaluation and treatment of stuttering in African Americans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…A study about African American perceptions about stuttering revealed that some African Americans believe that stuttering is caused when a mother eats improper foods while nursing, if a child gets a haircut before saying the first word, if a mother sees a snake during pregnancy, and if a child is scared by a person or event. 5 In another study, however, African American middle and high school students stated that they did not believe that stuttering can be caused by a baby being dropped on its head, by a child being tickled too much, by a person looking into a mirror as a baby, or by a dog biting a child. 17 Minimal information has been documented about Asian American perceptions about stuttering.…”
Section: Perceptionsmentioning
confidence: 98%
See 1 more Smart Citation
“…A study about African American perceptions about stuttering revealed that some African Americans believe that stuttering is caused when a mother eats improper foods while nursing, if a child gets a haircut before saying the first word, if a mother sees a snake during pregnancy, and if a child is scared by a person or event. 5 In another study, however, African American middle and high school students stated that they did not believe that stuttering can be caused by a baby being dropped on its head, by a child being tickled too much, by a person looking into a mirror as a baby, or by a dog biting a child. 17 Minimal information has been documented about Asian American perceptions about stuttering.…”
Section: Perceptionsmentioning
confidence: 98%
“…3 Apart from a few studies, multicultural issues in fluency disorders have been overlooked, especially in the areas of perceptions about stuttering, approaches to assessment and treatment, and prevalence estimates. [4][5][6][7] Experts have indicated that the prevalence of stuttering in the general population is about 1%, 8 however, prevalence estimates of 2.8% for African American high school students who stutter 9 and 2% for African American preschoolers who stutter 10 have been reported. Among Hispanic Americans, prevalence estimates of 0.29 6 to 0.84% 11 have been reported.…”
mentioning
confidence: 99%
“…The role of culture in stuttering has been addressed many times in various research articles and studies across the decades (Cooper & Cooper, 1998;Johnson, 1944;Leith, 1986;Leith & Mims, 1975;Olsen, Steelman, Buffalo, & Montague, 1999;Robinson & Crowe, 1998;Shames, 1989). However, as Shames (1989) suggested, limited research has examined cultural issues of people who stutter of historically disadvantaged race-ethnic groups.…”
Section: Introductionmentioning
confidence: 94%
“…As a result of the multiple issues that need to be considered when treating and describing stuttering, a number of researchers have begun to focus on personal qualitative accounts of people who stutter (Corcoran & Stewart, 1998;Crichton-Smith, 2002;Plexico, Manning, & DiLollo, 2005;Stewart & Richardson, 2004), in part responding to the recognition that stuttering involves more than disordered physical speech production (Smith, 1999;Yaruss & Quesal, 2004). It is not surprising then that researchers increasingly recognize that it is important to consider cultural experiences when working with people who stutter (Cooper & Cooper, 1998;Leith, 1986;Robinson & Crowe, 1998;Shames, 1989). Battle (1998) defined culture as "the behavior, beliefs, and values of a group of people who are brought together by their commonality" (p. 3).…”
Section: Introductionmentioning
confidence: 96%
“…It is unfortunate that in the area of fluency disorders, few published studies have examined the influence of cultural issues and racial and ethnic backgrounds of children who stutter (CWS). In spite of the changing demographics of caseloads and the general agreement of clinicians and researchers about the need for cultural responsiveness in assessment and treatment of stuttering, the majority of research in CWS has focused on predominantly White, non-Hispanic persons, excluding the samples' racial and cultural identities (Conrad & Seymour;1998;Finn & Cordes, 1997;Goldstein, 2000;Guitar, 2006;Manning, 2002;Robinson & Crowe, 1998Shapiro, 1999). It is interesting that reports of higher incidences of stuttering in African Americans when compared with Whites have been published (Brutten & Miller, 1988a, 1988bOlsen, Steelman, Buffalo, & Montague, 1999;Robinson, Davis, & Crowe, 2000).…”
Section: A Recent Issue Of Communication Disorders Quarterlymentioning
confidence: 97%